History, space and place - Rau, Susanne 1969- (Routledge, Taylor & Francis Group, 2019)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Acknowledgments -- Introduction: What is historical research into space? -- Why historical research into space is not new -- Why historical research into space is, in fact, new -- Chapter 1 Historical and systematic approach -- 1.1 Prehistory -- 1.2 Concepts -- Notes -- Chapter 2 Disciplinary approaches -- 2.1 Geography -- 2.2 Cultural anthropology, postcolonial studies -- 2.3 Sociology -- 2.4 Spaces and spatialities as a new historiographical topic -- Notes -- Chapter 3 Spatial analysis -- 3.1 Spatial constitution and configurations -- 3.2 Spatial dynamics: Emergence-transformation-dissolution -- 3.3 The subjective construction of spaces -- 3.4 Spatial practices-uses of space -- Notes -- Chapter 4 Conclusion and outlook -- Chapter 5 Appendix of sources for the historical study of space -- Sources for the analysis of spatial dimensions of historical societies -- Contents -- Part A: Conceptual history -- Part B: Sources on urban history and the history of trade -- Part C: Maps as media for representing spatial relations, creating spaces, and disseminating images of the world, and as instruments for orientation -- Notes -- Selected bibliography -- Literature -- Internet resources and portals -- Journals or special issues of journals -- Lexicon entries -- Glossary -- Afterword to the second edition -- Index.